Biventricular Reference Values by Body Surface Area, Age, and Gender in a Large Cohort of Well‐Treated Thalassemia Major Patients Without Heart Damage Using a Multiparametric CMR Approach. Issue 1 (20th April 2020) - Meloni, Antonella; Righi, Riccardo; Missere, Massimiliano; Renne, Stefania; Schicchi, Nicolò; Gamberini, Maria Rita; Cuccia, Liana; Lisi, Roberto; Spasiano, Anna; Roberti, Maria Grazia; Zuccarelli, Angelo; Ait‐Ali, Lamia; et al.
Abstract : Background: Cardiac MRI plays a critical role in the management of thalassemic patients. No accurate biventricular reference values are available. Purpose: To establish the ranges for normal left ventricular (LV) and right ventricular (RV) volumes and ejection fraction (EF) and LV mass normalized to body surface area (BSA), age, and gender in a large cohort of well‐treated beta‐thalassemia major (β‐TM) patients without heart damage using a multiparametric MRI. Study Type: Retrospective/cohort study. Population: In all, 251 β‐TM patients with no known risk factors or cardiac disease, normal electrocardiogram, no macroscopic myocardial fibrosis, and all cardiac segments with T2 * ≥20 msec, and 246 healthy subjects. Field Strength/Sequence: 1.5T/cine steady‐state free precession (SSFP), gradient‐echo T2 *, late gadolinium enhancement (LGE) images. Assessment: Biventricular end‐diastolic volume, end‐systolic volume, stroke volume, and LV mass were normalized to BSA (EDVI, ESVI, SVI). Statistical Tests: Comparisons between the two groups was performed with two‐samples t ‐test or Wilcoxon's signed rank test. For more than two groups, one‐way analysis of variance (ANOVA) or a Kruskal–Wallis test were applied. Results: Compared to controls, males with β‐TM showed significantlt higher LVEDVI in all the age groups, while for the other volumes the difference was significant only within one or more age groups. In females the volumes were comparable between β‐TM patients and healthy subjects in all the age groups. In the male β‐TM population we found a significant effect of age on LVEDVI ( P = 0.017), LVESVI ( P = 0.001), RVESVI ( P = 0.029), and RVEF ( P = 0.031), while for females none of the biventricular parameters were significantly different among the age groups (LVEDVI: P = 0.614; LVESVI: P = 0.449; LVSVI: P = 0.186; LV mass index: P = 0.071; LVEF: P = 0.059; RVEDVI: P = 0.374; RVESVI: P = 0.180; RVSVI: P = 0.206; RVEF: P = 0.057). In β‐TM patients all biventricular volume indexes as well as the LV mass index were significantly larger in males than in females ( P  < 0.0001 in all cases). The LV and the RV EF were comparable between the sexes ( P = 0.568 and P = 0.268, respectively). Data Conclusion: Appropriate "normal" reference ranges normalized to BSA, sex, and age are recommended to avoid misdiagnosis of cardiomyopathy in β‐TM patients. Level of Evidence: 4 Technical Efficacy Stage: 2